Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12886-018-0727-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of corneal cross-linking in vitro and in vivo for Fusarium solani: a potential new treatment for fungal keratitis

Abstract: BackgroundFungal keratitis is one of the major causes of visual impairment worldwide. However, the effectiveness of corneal collagen cross-linking (CXL) for fungal keratitis remains controversial. In this study, we developed an in vitro and an in vivo models to assess the efficacy of CXL for Fusarium keratitis.MethodsThe effect of in vitro CXL fungicidal was evaluated on the cultures of Fusarium solani which were exposed to irradiation for different durations. Viability of fungal was appraised under four condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Only a healthy ocular surface can provide a smooth optical surface for visual function and a normal tear film plays a dominant role in it 31 . Though tear film instability, which might be the initiator of severe ocular surface disease, has not yet been reported in myopic children under atropine control, it was recently announced and noticed as an unignorable risk in children under orthokeratology control 12,13,15,32 . Some researchers debated about the ocular surface alterations after overnight wearing of orthokeratology lenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a healthy ocular surface can provide a smooth optical surface for visual function and a normal tear film plays a dominant role in it 31 . Though tear film instability, which might be the initiator of severe ocular surface disease, has not yet been reported in myopic children under atropine control, it was recently announced and noticed as an unignorable risk in children under orthokeratology control 12,13,15,32 . Some researchers debated about the ocular surface alterations after overnight wearing of orthokeratology lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 12 reported that overnight wearing of orthokeratology lenses could decrease TMH and TBUT but did not affect the function of the meibomian glands. However, Li et al 32 and Xie et al 13 pointed out that basal tear secretion and ocular surface inflammation were unaffected after orthokeratology treatment and there was only a short-term decrease in TBUT. They believed that the increase in tear evaporation may be related to the distribution of tear film caused by transient morphological changes in the tear film.…”
Section: Discussionmentioning
confidence: 99%
“…One such experimental workflow in this regard is as follows: a 2 mm diameter trephine is used to mark the central cornea, and then a size-11 scalpel blade is used to cut into the epithelium within the marked area. Then, a sharpened bamboo toothpick is used to debride and smear F. solani mycelium onto the ocular surface [ 42 , 43 , 44 , 45 , 46 ]. Such a method can also be used for A. fumigatus as demonstrated in Figure 2 B (unpublished data).…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…Separate from Acanthamoeba keratitis, the typical clinical features of fungal keratitis are difficult to ascertain in the early stage of infection, leading to common misdiagnoses and delayed treatment [4, 5]. Although there are new therapies used in clinical application, fungal keratitis remains a challenge to ophthalmologists due to a lack of effective drugs after late initiation of treatment secondary to delayed diagnosis [6, 7].…”
Section: Introductionmentioning
confidence: 99%